The Recategorization of the Rheme and the Structure of the Oral Paragraph in French and in Finnish - Mari Lehtinen (Discours)
At first sight, the intonation systems of French and Finnish – which are typologically distant languages – seem completely different. This paper aims, however, at showing that the discourse-structuring role of the utterance-final pitch rises in spontaneous spoken Finnish is in many respects reminiscent of the final pitch rises that constitute an essential component of the French intonation system (Morel & Danon-Boileau, 1998). Indeed, in both cases, utterance-final pitch rises occurring inside a multi-unit turn seem to “recategorise the rheme as a preamble” for what will follow (Morel & Danon-Boileau, 1998). ‘Preamble’ and ‘rheme’ are the two main constituents of the so-called ‘oral paragraph’, which is the basic structural unit of French discourse according to their model. In addition to comparing the realization of the so-called ‘recategorization phenomenon’ in French and in Finnish, this paper aims at describing the structure of the ‘oral paragraph’ of Finnish within Morel and Danon-Boileau’s framework.